Analysis of Anemia Prevention Factors in Pregnant Women Based on Information-Motivation-Behavioral (IMB) Theory in the Work Area of the Kalianget Health Center - Eka Mieri Kurniyati; Mujib Hannan; Zakiyah Yasin; Abd. Wahid (Knowledge Dynamics, 2026)
Background: Anemia in pregnant women is one of the health problems that is still a challenge in Indonesia, including the Kalianget Health Center. Anemia can have a profound impact on both the mother and the fetus that is conceived. The prevention of anemia is highly dependent on pregnant women's knowledge, motivation, and behavior. This study analyzes the relationship between information and motivation for preventing anemia in pregnant women based on the theory of Information Motivation Behavior (IMB). Methods: The study used an observational design with a cross-sectional approach. The sample consisted of 35 pregnant women selected by simple random sampling. The research instrument used questionnaires and hemoglobin level checks. Results: showed that most respondents had moderate information and motivation. There was a significant relationship between information and anemia prevention (p = 0.000; r = 0.713) and between motivation and anemia prevention (p = 0.000; r = 0.743). Conclusion: It can be concluded that the higher the level of information and motivation of pregnant women, the better the anemia prevention behavior that is carried out. The IMB theoretical approach has been proven effective in supporting health promotion efforts to reduce the risk of anemia in pregnant women.